Controllable Mono‐/Dialkenylation of Benzyl Thioethers through Rh‐Catalyzed Aryl CH Activation. Issue 36 (16th August 2013) - Zhang, Xi‐Sha; Zhu, Qi‐Lei; Zhang, Yun‐Fei; Li, Yan‐Bang; Shi, Zhang‐Jie
<x xml:space="preserve">Abstract</x> Under solvent control: Benzyl thioethers were alkenylated in excellent yields with broad substrate scope and the selectivity (mono‐ vs. disubstituted product) was controlled by the solvent and ratio of reactants (see scheme). Sequential alkenylation with two different alkenes was also carried out in a one‐pot process. In addition, the thioether directing group was removed in a one‐pot process with simultaneous hydrogenation of the double bond to give the toluene derivatives.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>